Effect of fat content in polyphenols concentration and antioxidant capacity of Theobroma cacao L."cacao" - Del Rosario Castro, Marili (2017)
Cocoa beans (Theobroma cacao L.), were processed to four days of fermentation and seven days of natural drying. The content of total polyphenols was determined by Folin-Ciocalteu method. Most abundant polyphenols in cocoa are metabolits catechin flavonoid type, anthocyanins and proanthocyanins. Most of them are responsible for the antioxidant and their concentration may vary by factors such as temperature, fermentation, drying or effects due to fat content in the composition. Polyphenols content in cocoa bean with and without fat was 5,39±0,26% and 6,26±0,26%; respectively. On the other hand, antioxidant capacity with and without fat was 337,42±19,27 and 411,15±11,72 mM equivalents to TROLOX/g ms; respectively. The polyphenol content and antioxidante capacity between beans with and without fat showed significant differences (p<0,05), being defatted cocoa beans the high content of polyphenols and antioxidant capacity resulting as an effective process to the improvement of nutritional quality.